Integrating fundamental processes to understand eco‐evolutionary community dynamics and patterns. (26th July 2021) - Govaert, Lynn; Altermatt, Florian; De Meester, Luc; Leibold, Mathew A.; McPeek, Mark A.; Pantel, Jelena H.; Urban, Mark C.
Abstract: Recent studies demonstrate that ecological and evolutionary processes can occur over similar temporal and spatial scales and might thus frequently interact. Although concepts such as the evolving metacommunity, diffuse (co)evolution and community genetics integrate multi‐species dynamics, most experimental studies usually consider how evolution affects only one focal species. Hence, our understanding of evolution in multi‐species communities is still underdeveloped. We highlight key community and evolutionary mechanisms and their interactions to facilitate a broader understanding of evolution in multi‐species communities. We propose a framework that explicitly considers interactions between each of the four analogous processes of evolutionary biology (selection, gene flow, genetic drift and mutation) and community ecology (species sorting, dispersal, ecological drift and speciation). Focusing on interactions between processes of evolutionary biology and community ecology enables explorations of the full range of eco‐evolutionary dynamics in multi‐species communities and guides the design of novel experiments. Furthermore, the proposed framework develops a shared language between evolutionary biologists and community ecologists and indicates new research avenues. Overall, we propose that explicitly incorporating interactions between these evolutionary and community processes to study eco‐evolutionary dynamics in multi‐species communities will better inform broader questions about the maintenance of diversity and the resilience of diverse communities to disturbances, both natural and manmade. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Zusammenfassung: Aktuelle Studien zeigen, dass ökologische und evolutionäre Prozesse über ähnliche zeitliche und räumliche Skalen ablaufen und somit häufig interagieren können. Obwohl Konzepte wie die sich evolutionär verändernde Meta‐Lebensgemeinschaft, die diffuse (Ko‐)Evolution und die Genetik von Lebensgemeinschaften die Dynamik mehrerer Arten integrieren, betrachten die meisten experimentellen Studien normalerweise nur, wie sich Evolution auf eine Fokusart auswirkt. Daher ist das Verständnis der Evolution in artenreichen Lebensgemeinschaften noch unterentwickelt. Wir beleuchten die wichtigsten Lebensgemeinschafts‐ und Evolutionsmechanismen und ihre Interaktionen, um ein breiteres Verständnis der Evolution in artenreichen Lebensgemeinschaften zu ermöglichen. Wir schlagen einen konzeptionellen Rahmen vor, der explizit die Interaktionen zwischen jedem der vier analogen Prozesse der Evolutionsbiologie (Selektion, Genfluss, genetische Drift und Mutation) und der Gemeinschaftsökologie (Artensortierung, Ausbreitung, ökologische Drift und Artbildung) berücksichtigt. Die Fokussierung auf die Wechselwirkungen zwischen evolutionsbiologischen und gemeinschaftsökologischen Prozessen ermöglicht die Erforschung des gesamten Spektrums öko‐evolutionärer Dynamiken in artenreichen Lebensgemeinschaften sowie das Design neuartiger Experimente. Darüber hinaus entwickelt der vorgeschlagene konzeptionelle Rahmen eine gemeinsame Sprache zwischen Evolutionsbiologen und Gemeinschaftsökologen und zeigt neue Forschungswege auf. Generell schlagen wir die explizite Einbeziehung von Interaktionen zwischen diesen evolutionären und synökologischen Prozessen zur Untersuchung der öko‐evolutionären Dynamiken in artenreichen Lebensgemeinschaften vor. Dies ermöglicht ein umfassenderes Verständnis, wie die Diversität und Resilienz verschiedener Lebensgemeinschaften gegenüber natürlichen und menschengemachten Störungen aufrecht erhalten werden kann.